The Effectiveness of Web Graphic Organizer to Enhance Students’ Writing Skill on Descriptive Text - Laila Jaha; As'ari As'ari; Tri Ilma Septiana (Jurnal Sosiologi Pendidikan Kolaboratif, 2025)
This research aims to measure the effectiveness of using Web Graphic Organizer to enhance student’s writing skill on descriptive text. There were three research questions proposed in this study, namely: 1) How are the students writing skill on descriptive text before treatment? 2) How the implementation of web graphic organizer 3) How is the effectiveness of Web Graphic Organizer to enhance student’s writing skill on descriptive text. The research design of this study consist of pre-test, treatment and post-test. The final finding of this study showed that t0 on degree of significance 5% that was 1.67 Therefore, the result of t-test showed that t0 < tt or 3.43 > 1.67. In brief, t-test show that Ha or alternative hypothesis was accepted. The hypothesis test shows the effect size in this study is 0.85, while strong effect category is (0.51->1.00). In other words, It can be drawn a conclusion that there is a significant effect of using Web Graphic Organizer to enhance student’s writing skill on descriptive text at the tenth grade of MA Raudhlatul Ulum Anyer.